Evaluation of endogenous intoxication indicators in the dynamics of experimental periodontitis and immobilization stress - Olekshij, P. (Journal of Education, Health and Sport, 2021)
The aim of our work was to investigate the peculiarities of changes in endogenous intoxication rates: medium mass molecules (MMM) and erythrocyte intoxication index (EII) in the blood of guinea pigs in the formation of combined pathology - experimental periodontitis (EP) and immobilization stress (IS).The results of biochemical studies showed that at all stages of development of combined pathology - experimental periodontitis and immobilization stress there is a consistent increase in the degree of endogenous intoxication, which dominated on the 15th day of the experiment, namely increased content of medium mass molecules (МMМ254 , MMM280) and EII in the blood by 58.5% (p≤0.05), 80.3% (p≤0.05) and 95.7% (p≤0.05), respectively, compared with the first group of animals is a clear manifestation of the formation of endogenous intoxication. These changes are obviously the result of insufficient elimination of toxic products on the background of the inflammatory process in periodontal tissues and stress.